From firm to soft: Maturity-driven mechanical damage behavior of apples - Zixu Chen; Linlong Jing; Ruofei Liu; Huawei Yang; Linlin Sun; Xinpeng Cao; Yongxian Wang; Shenghui Fu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2026)

Curvature sensing strategy for flexible gripper fingers during grasping deformation: enabling in-orchard online apple size grading - Guangze Zhao; Hongjian Zhang; Jingwei Sun; Huawei Yang; Shaowei Wang; Shuangxi Liu; Xinpeng Cao; Shenghui Fu; Yongxian Wang; Linlin Sun; Linlong Jing; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Nonlinear long waves over a rigid porous seabed - Linlong Tong; Chao Xu; Jisheng Zhang; Zhiyuan Yang; Haoran Li; Xianju Xie (Ocean Engineering, 2025)

Core-sheath structured CNT@Ni-CNT fiber-based multifunctional fabric with high-sensitivity, wide-range strain sensing, and enhanced electromagnetic shielding absorption - Yiqian Shao; Lihua Zou; Yang Chen; Lirui Wang; Linlong Song; Hang Xu; Ping-an Yang (Chemical Engineering Journal, 2025)

Multiple environmental factors drive the functional dimension of fish communities in the Central East China Sea - Pengzhan Zhang; Yang Liu; Yang Yan; Linlong Wang; Yefu Kong; Xin Peng; Bin Kang (Marine Environmental Research, 2025)

Rapidly synthesizing magneto-thermal adjustable high entropy alloy nanoparticles on carbon fiber surface for enhancing electromagnetic wave absorption, thermal conductivity and interface compatibility of composites - Jinchuan Chen; Chuanqiang Sun; Zhe Han; Yujing Zhang; Feng Yang; Linlong Xing; Huajie Xu; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2024)

From tissue lesions to neurotoxicity: The devastating effects of small-sized nanoplastics on red drum Sciaenops ocellatus - Zhicheng Sun; Xin Peng; Linlin Zhao; Yi Yang; Yugui Zhu; Linlong Wang; Bin Kang (Science of The Total Environment, 2024)

Prioritizing the multifaceted community and species uniqueness for the conservation of lacustrine fishes in the largest subtropical floodplain, China - Yang Liu; Yang Yan; Li Lin; Linlong Wang; Yanping Zhang; Bin Kang (Journal of Environmental Management, 2024)

Simultaneous manipulation of constituent and structure toward MOFs-derived hollow Co3O4/Co/NC@MXene microspheres via pyrolysis strategy for high-performance microwave absorption - Linlong Xing; Haoran Cheng; Yang Li; Qiang Chen; Xianhu Liu (Chemical Engineering Journal, 2024)

The Impact of Pre-Existing Faults on Fault Geometry during Multiphase Rifts: The Jiyang Depression, Eastern China - Di Wang; Linlong Yang; Wei Li; Xidong Wang (Journal of Marine Science and Engineering, 2023)
The combination of multi-phase extension and pre-existing fault reactivation results in a complex fault pattern within hydrocarbon-bearing basins, affecting hydrocarbon exploration at different stages. We used high-resolution 3D seismic data and well data to reveal the impact of multi-phase extension and pre-existing fault reactivation on Cenozoic fault pattern changes over time in the Jiyang Depression of eastern China. The results show that during the Paleocene, a portion of NW-striking pre-existing faults reactivated under NS extension and controlled the basin structure (type 1). Other parts of the NW-striking pre-existing faults stopped activity and served as weak surfaces, and a series of NNE-striking faults were distributed in an en-echelon pattern along the NW direction at shallow depths (type 2). In areas unaffected by pre-existing faults, NE-striking faults formed perpendicular to regional stresses. During the Eocene, the regional stresses shifted clockwise to near-NS extension, and many EW-striking faults developed within the basin. The NE-striking faults and the EW-striking faults were hard-linked, forming the ENE-striking curved faults that controlled the structure in the basin (type 3). The NNE-striking faults were distinctly strike-slip at this time, with the ENE-striking faults forming a horsetail pattern at their tails. Many ENE-striking faults perpendicular to the extension direction were formed in areas where the basement was more stable and pre-existing faults were not developed (type 4). There were also developing NS-striking faults that were small in scale and appeared in positions overlapping different main faults (type 5). Additionally, different fault patterns can guide different phases of hydrocarbon exploration. Type 1, type 2, and type 3 faults are particularly suitable for early-stage exploration. In contrast, type 4 and type 5 faults are more appropriate for mature exploration areas, where they may reveal smaller hydrocarbon reservoirs.

Superhydrophobic graphene nanowalls for electromagnetic interference shielding and infrared photodetection via a two-step transfer method - Qi Yang; Jun Yang; Linlong Tang; Heng Zhang; Dapeng Wei; Haofei Shi; Xingzhan Wei; Yupeng Zhang; Bin Su (Chemical Engineering Journal, 2023)

Stable Isotope Analysis Revealed Ontogenetic Changes in Trophic Ecology and Migration Patterns of Sepia esculenta in the Northern Coastal Waters of China - Linlong Wang; Yang Liu; Xiumei Zhang (Frontiers in Marine Science, 2022)
Golden cuttlefish ( Sepia esculenta ), the most economically important cephalopod in the northern coastal seas of China, had experienced greatly reduced population biomass due to continuous fishing pressure in recent decades. Understanding the trophic ecology and clarifying the spatial distribution of wintering ground can help develop management plans for this species. In this study, the ontogenetic changes in the trophic ecology of S. esculenta in the Qingdao coastal water were determined, and the migration patterns were studied using stable isotope analysis. Cluster analysis based on isotopic values divided S. esculenta with different lengths into groups: 11–20, 21–100, and 121–200 mm. A significant difference in the δ 13 C values between the groups 11–20 mm (−17.10‰) and 21–100 mm (−15.89‰) illustrates an ontogenetic change in the feeding habits. Due to the migratory habits of S. esculenta , the δ 13 C value of the group 121–200 mm (−16.39‰) was lower than that of the group 21–100 mm. The δ 15 N values of S. esculenta were found to increase in length, and there was a clear linear relationship between different S. esculenta groups, suggesting that the wintering ground may locate in the same latitude as the spawning ground (i.e., the middle Yellow Sea). Furthermore, the trophic relationship between S. esculenta and coexisting species was assessed, revealing that the group 11–20 mm of S. esculenta has some overlap of carbon isotope space with other species, suggesting that these species may feed on it as prey. Thus, slightly increasing the length to more than 20 mm may reduce the pressure of being the prey of post-release juveniles of S. esculenta and improve the effect of release.

Fishery Status and Rebuilding of Major Economic Fishes in the Largest Freshwater Lake in China Based on Limited Data - Yang Liu; Huiyun Fu; Linlong Wang; Li Lin; Gang He; Peifeng Fu; Changlai Wang; Yanping Zhang; Bin Kang (Fishes, 2022)
Poyang Lake, the largest freshwater lake in China, possesses abundant fishery resources, but its fish stock status is still unclear. In this work, the stock status of and fishing efforts of nine major economic fishes in the Poyang Lake were estimated from 2000 to 2019 with a catch-based maximum sustainable yield (CMSY) model based on catch and resilience data. It was further predicted whether the biomass of those fishes could be restored to support maximum sustainable yield (Bmsy) under the policy of “Ten years fishing moratorium in the Yangtze River”. The results showed that goldfish Carassius auratus, grass carp Ctenopharyngodon idella, and black carp Mylopharyngodon piceus suffered from higher fishing efforts and low biomass in the past 20 years; bighead carp Hypophthalmichthys nobilis, yellow catfish Tachysurus fulvidraco, and common carp Cyprinus carpio responded differently to their fishing efforts; silver carp Hypophthalmichthys molitrix, Amur catfish Silurus asotus, and mandarin fish Siniperca chuatsi were underexploited. Six species were overfished in 2019, and their biomass would be expected to recover for sustainable exploitation during the fishing moratorium, except for M. piceus. This study provided a case study of feasible freshwater fishery evaluation in limnetic ecosystems.

Fishery Dynamics, Status, and Rebuilding Based on Catch-Only Data in Coastal Waters of China - Linlong Wang; Li Lin; Yang Liu; Lu Zhai; Shen Ye (Frontiers in Marine Science, 2022)
China has become the largest contributor to marine fisheries in the world with its fishing fleets explosively increasing their fishing effort and resulting catch, but its fishery composition and sustainability have deteriorated. Limited information on fishery exploitation status encumbers effective resource management. In this study, a data-poor Monte Carlo method, the Catch-Maximum Sustainable Yield (CMSY) method, was used to estimate the historical exploited dynamics and current stock status of ten Chinese economic marine fish stocks, including Trichiurus lepturus , Larimichthys crocea , Larimichthys polyactis , Thamnaconus modestus , Scomberomorus niphonius , Ilisha elongate , Decapterus maruadsi , Scomber japonicus , Engraulis japonicus , and Clupea pallasii , which accounted for about 50% of total fish catches in the coastal waters of China and covered five functional groups (i.e., large, medium benthopelagic, large, medium, and small pelagic). Species L. crocea and L. polyactis had been subjected to overfishing since the 1950s. The others showed a decreasing trend in biomass along with the explosively increasing fishing efforts since the 1990s. Benthopelagic fish experienced overfishing pressure about a decade earlier than pelagic species. All the fish stocks investigated in this study were depleted (current biomass lower than the biomass capable of producing maximum sustainable yields, i.e., B < B msy ) in 2019, and most species were still facing high-fishing pressure (current fishing mortality higher than the mortality capable of producing maximum sustainable yields, i.e., F > F msy ). Also, a Schaefer model was used to assess stocks rebuilding status until 2030 under four exploitation scenarios, i.e., fishing mortality equals 0.5, 0.6, 0.8, or 0.95 times F msy . Most species stocks will likely recover to the B msy , which indicates that reduction of fishing pressure is probably the most effective way for fishery recovery.

Quantitative Analysis of Faults in Huizhou Sub-basin, Pearl River Mouth Basin - Boubacar Hamidou Leyla; Junxia Zhang; Linlong Yang (Journal of Earth Science, 2018)

Seismic reflection characteristics and evolution of intrusions in the Qiongdongnan Basin: Implications for the rifting of the South China Sea - Yanghui Zhao; Dianjun Tong; Ying Song; Linlong Yang; Chao Huang (Journal of Earth Science, 2016)

Characterising the nature, evolution and origin of detachment fault in central depression belt, Qiongdongnan Basin of South China Sea: evidence from seismic reflection data - Jianye Ren; Daojun Zhang; Dianjun Tong; Anmin Huang; Yahui Wang; Chao Lei; Qianmei Zuo; Yanghui Zhao; Weijun He; Linlong Yang (Acta Oceanologica Sinica, 2014)